2015
DOI: 10.11604/pamj.2015.21.291.6831
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the magnitude and associated factors of immunological failure among adult and adolescent HIV-infected patients in St. Luke and Tulubolo Hospital, Oromia Region, Ethiopia

Abstract: IntroductionThe use of antiretroviral therapy (ART) has become a standard of care for the treatment of HIV infection. However, cost and resistance to ART are major obstacles for access to treatment especially in resource-limited settings. In this study, we aimed to assess the magnitude and associated factors of Immunological failure among adult and adolescent HIV infected Patients (with age ‘15yrs) on Highly Active Antiretroviral Therapy (HAART) in St. Luke and Tulu Bolo Hospitals, Oromia Region, Ethiopia.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
3
11
2
Order By: Relevance
“…This is in agreement with the findings of a study conducted at St. Luke and Tulu Bolo Hospitals, South West Shoa Zone, Oromia [18,27]. However, it is dissimilar with the findings from a study in Tanzania [23].…”
Section: Discussionsupporting
confidence: 79%
“…This is in agreement with the findings of a study conducted at St. Luke and Tulu Bolo Hospitals, South West Shoa Zone, Oromia [18,27]. However, it is dissimilar with the findings from a study in Tanzania [23].…”
Section: Discussionsupporting
confidence: 79%
“…This study showed, not disclosing HIV status to family or other persons was associated with an increased risk of treatment failure. The finding is in line with a study conducted at St. Luke and Tulu bolo Hospital, 14 but it contrasts with the study conducted in Addis Ababa private facilities, which showed HIV patients who did not disclose their HIV status had a lower risk of treatment failure. 12 HIV status disclosure could have positive benefits such as high social support, stronger family cohesion, and relationships, reductions in anxiety and depression, good adherence to medication and improvements in physical health which might lead to better respond to treatment.…”
Section: Discussionsupporting
confidence: 76%
“…13 But, this finding contrasts with the studies conducted in St. Luke and Tulu Bolo hospitals and Tanzania, which indicated baseline functional status did not have an association with the hazard of treatment failure. 14,25 This inconsistency could be due to differences in criteria used to measure ART failure and follow -up period across studies. Bedridden functional status ART initiation reflects the deprived health condition and immunologic deterioration of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia, first-line ART treatment failure is 19.8% (immunologic 15%, clinical 6.3%, and virologic failure 1.3%) among adult PLWHA who are on ART according to the report from private health facilities in Addis Ababa [14]; Immunologic and clinical failure was 19.7 % and 19.5 % respectively as reported from Southwest Ethiopia [15]. Documented findings from the University of Gondar referral hospital, Debremarkos, St. Luke and Tulubolo hospitals showed that immunologic failures were 22.2%, 21%, and 6.8%, respectively [16][17][18].…”
Section: Introductionmentioning
confidence: 99%